Mathematics coordinators as school team PD leaders before and during COVID-19 - Cohen-Nissan, Orit; Kohen, Zehavit (Teaching and Teacher Education, 2023)
This study explored a professional development (PD) program preparing mathematics coordinators to lead effective PD in their schools. Due to the COVID-19 pandemic emerging in the midst of this study, the PD program and school team PD were performed online instead of face-to-face. We explored the PD program and school team PD design before and during COVID-19 period, and the coordinators' expertise-based PD leadership professional identity (LPI). Findings revealed structural stability of the PD program design, and support of coordinators’ LPI. Coordinators enacted a structural transition of effective PD design into the school team PD, demonstrating their LPI in practice.
Keywords: COVID-19 pandemic; Effective PD programs; PD leaders; Professional identity; Professional learning community